2022
DOI: 10.1007/s10880-022-09921-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pain Catastrophizing, Emotional Intelligence, and Pain Intensity in the Quality of Life of Cancer Patients with Chronic Pain

Abstract: Pain catastrophizing (PC) is a negative cognitive distortion to actual or anticipated pain. This study aims to investigate the relationship between pain catastrophizing, emotional intelligence, pain intensity, and quality of life (QoL) in cancer patients with chronic pain. Eighty-nine outpatients with chronic pain attending pain clinics and palliative care units were recruited. Participants were men (42.7%) and women (57.3%) with an average age of 56.44 years (SD = 14.82). Self-report psychological measures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…More participants (34, 57%) attributed their chronic pain to unrelated comorbidities than to cancer treatment (15, 25%). Old injuries (accidents at work, school, home, or involving motor vehicles) were commonest (n=11), followed by other medical diagnoses (8), post-operative pain (2), other unspeci ed causes (7), and no obvious cause (6).…”
Section: Chronic Pain According To Attributed Originmentioning
confidence: 99%
See 1 more Smart Citation
“…More participants (34, 57%) attributed their chronic pain to unrelated comorbidities than to cancer treatment (15, 25%). Old injuries (accidents at work, school, home, or involving motor vehicles) were commonest (n=11), followed by other medical diagnoses (8), post-operative pain (2), other unspeci ed causes (7), and no obvious cause (6).…”
Section: Chronic Pain According To Attributed Originmentioning
confidence: 99%
“…They are known to contribute to cancer-related pain. [6,7] Cognitive and behavioral therapies have shown e cacy in modifying these factors and improving chronic pain outcomes,[8] yet access to these therapies remains limited [9].…”
Section: Introductionmentioning
confidence: 99%
“…The PCS is a measure of catastrophizing in the context of actual or anticipated pain. 9 The PCS measures catastrophizing as a multifaceted construct with three subscales: rumination, magni cation, and helplessness. PCS was used to digitize the patients in order to identify individuals who may be more vulnerable to higher pain responses.…”
Section: Pain Catastrophizing Scalementioning
confidence: 99%
“…A psychological factor which has consistently been shown to exert its influence on pain is a cognitive process referred to as pain catastrophizing. Numerous studies in the last thirty years have found it to be a strong predictor of pain intensity and disability across different clinical populations [ 5 ]. While it has been defined in many ways, most definitions of pain catastrophizing include an emphasis on the role of magnification of the threat value of pain, and the feeling of helplessness related to the experience of pain.…”
Section: Introductionmentioning
confidence: 99%